2019
DOI: 10.1101/712323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADCK4 deficiency destabilizes the coenzyme Q complex, which is rescued by 2,4-dihydroxybenzoic acid treatment

Abstract: AbstractADCK4 mutations usually manifest as steroid-resistant nephrotic syndrome, and cause coenzyme Q10 (CoQ10) deficiency. However, the function of ADCK4 remains obscure. We investigated ADCK4 function using mouse and cell models. Podocyte-specific Adck4 deletion in mice significantly reduced survival and caused severe focal segmental glomerular sclerosis with extensive interstitia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…106 Moreover, COQ8B/ADCK4 is required for CoQ 10 biosynthesis and mitochondrial function in podocytes. 121 Compared to other CoQ 10 biosynthesis defects, mutations in COQ8B/ADCK4 seem to result in a less severe clinical entity, with a more prominent kidney phenotype, higher age at onset of SRNS, and good patient survival owing to the lack of extrarenal manifestations. The selective glomerular phenotype of patients with COQ8B/ADCK4 mutations may be the result of relative enrichment of COQ8B/ADCK4 and lacking expression of the related protein COQ8A/ADCK3 in podocytes, whereas COQ8A/ADCK3 expression exceeds that of COQ8B/ADCK4 in most other body tissues.…”
Section: Diagnostic Methods and Monitoringmentioning
confidence: 98%
See 1 more Smart Citation
“…106 Moreover, COQ8B/ADCK4 is required for CoQ 10 biosynthesis and mitochondrial function in podocytes. 121 Compared to other CoQ 10 biosynthesis defects, mutations in COQ8B/ADCK4 seem to result in a less severe clinical entity, with a more prominent kidney phenotype, higher age at onset of SRNS, and good patient survival owing to the lack of extrarenal manifestations. The selective glomerular phenotype of patients with COQ8B/ADCK4 mutations may be the result of relative enrichment of COQ8B/ADCK4 and lacking expression of the related protein COQ8A/ADCK3 in podocytes, whereas COQ8A/ADCK3 expression exceeds that of COQ8B/ADCK4 in most other body tissues.…”
Section: Diagnostic Methods and Monitoringmentioning
confidence: 98%
“…130 A potential role for 2,4diHB was suggested for the treatment of CoQ10 deficiency caused by COQ8B/ADCK4 mutations as well. 121 Moreover, Ozeir et al demonstrated that analogs of 4-HB can bypass a deficient CoQ biosynthetic enzyme. 103 Additionally, hydroxylated analogues of 4-HB, 3,4-dihydroxybenzoic acid and/or vanillic acid were marked as a potential therapeutic intervention for CoQ 10 deficiency due to a COQ6 mutation.…”
Section: Treatmentmentioning
confidence: 99%
“…In this issue of JASN, a study by Widmeier et al 6 demonstrates that Adck4 function is required for podocyte maintenance and homeostasis in mice by stabilizing the CoQ complex ( Figure 1). Using whole-exome sequencing in patients with SRNS, this group was first to identify homozygous loss-of-function mutations in ADCK4 as disease causative.…”
mentioning
confidence: 99%
“…Interestingly, a group of mutations in genes involved in coenzyme Q 10 (CoQ 10 ; ubiquinone) biosynthesis, such as COQ 6 ; COQ 2 ; prenyl diphosphate synthase, subunit 2 (PDSS2); and ADCK4 (COQ8B), have also been associated with childhood-onset FSGS and SRNS. CoQ 10 is a component of the mitochondrial inner membrane and plays important roles in supporting electron transport of oxidative phosphorylation (OXPHOS), protection from oxidative stress, and activation of mitochondrial enzymes required in metabolic pathways, including pyrimidine synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation